Modern Etruscans Close Encounters with a Distant Past - Zampieri, Chiara; Piperno, Martina; Van den Bossche, Bart (Leuven University Press, 2023)
New insights on the reception of Etruscan antiquity in the modernist period. "L'Étrurie est à la mode", French archaeologist Salomon Reinach bluntly stated in 1927. Since the beginning of the nineteenth century, Etruria had not only been attracting the attention of archaeologists and specialists of all sorts, but it had also been a fascinating and, in some cases, captivating destination for poets, novelists, painters and sculptors from all over Europe. This volume deals with the impact of the constantly expanding knowledge on the Etruscans and their mysterious civilisation on Italian, French, English, and German literature, arts and culture, with particular regard to the modernist period (1890-1950). The volume brings a distinctive point of view to the subject by approaching it from an interdisciplinary and comparative perspective, and by looking at a quite diverse range of topics and artefacts, which includes, but is not limited to, the study of drawings, art works, travel essays, novels, cooking recipes, schoolbooks, photographs, and movies. By exploring a new paradigm to understand ancient cultures, beyond the traditional ideas and models of "reception of the classics", and by challenging the alleged fracture between the so-called "two cultures" of humanities and natural sciences, Modern Etruscans will be of interest to scholars from various disciplines. Designed as a learning tool for university courses on the interplay between literature and science in the twentieth century, it is suited as recommended reading for students in the humanities. Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).